2013
DOI: 10.1371/journal.pone.0058013
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Sequence of Prion Protein Consists an Epitope Specific to the Abnormal Isoform of Prion Protein (PrPSc)

Abstract: The conformation of abnormal prion protein (PrPSc) differs from that of cellular prion protein (PrPC), but the precise characteristics of PrPSc remain to be elucidated. To clarify the properties of native PrPSc, we attempted to generate novel PrPSc-specific monoclonal antibodies (mAbs) by immunizing PrP-deficient mice with intact PrPSc purified from bovine spongiform encephalopathy (BSE)-affected mice. The generated mAbs 6A12 and 8D5 selectivity precipitated PrPSc from the brains of prion-affected mice, sheep,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
1
9
1
Order By: Relevance
“…e,f) could allow for selection of the desired mAbs. On the other hand, in the epitope mapping of 8D5 and 6A12, PrP Sc ‐specific mAbs recently generated by our group, Pepspot revealed that these mAbs recognize almost the same region, that is, PrP31–39 and PrP41–47, respectively . This finding supports the idea that the N‐terminus of PrP Sc harbors a PrP Sc ‐specific conformation.…”
Section: Evaluation Of Antisera Binding To the N‐terminal Region By Esupporting
confidence: 75%
“…e,f) could allow for selection of the desired mAbs. On the other hand, in the epitope mapping of 8D5 and 6A12, PrP Sc ‐specific mAbs recently generated by our group, Pepspot revealed that these mAbs recognize almost the same region, that is, PrP31–39 and PrP41–47, respectively . This finding supports the idea that the N‐terminus of PrP Sc harbors a PrP Sc ‐specific conformation.…”
Section: Evaluation Of Antisera Binding To the N‐terminal Region By Esupporting
confidence: 75%
“…However, the detailed threedimensional structures of PrP Sc and its variants remain a mystery. One approach to probing prion structures and studying prion pathogenesis has been the development of PrP Sc -and/or PrP RESselective antibodies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Despite some successes, the development of PrP Sc -specific antibodies with diverse epitopes has been limited by the fact that PrP Sc has the same primary sequence as PrP C .…”
mentioning
confidence: 99%
“…Moreover, a novel PrP Sc -specific epitope has been recently reported in the region aa31-aa47 by using mAbs raised against intact PrP Sc complexes (Masujin et al 2013). Surprisingly, in our panel, mAb EB8 failed to promote prion clearance as efficiently as the other antibodies.…”
Section: Discussioncontrasting
confidence: 49%